Analisis Efektivitas Penerapan Protokol Kesehatan Selama Masa Pandemi Covid-19 Bagi Penumpang di Bandar Udara Internasional Soekarno-Hatta: - - Alwi Himawan (Jurnal Multidisiplin Madani, 2022)
End of 2019, the world was haunted by a deadly disease, namely COVID-19, to stop its spread, the government implemented health protocols. Therefore, this study was conducted to determine effectiveness of health protocol during the pandemic that implemented at Soekarno-Hatta International Airport from the passenger's perspective. This research was conducted during February 2022, by distributing questionnaires using Google Forms. Domestic passengers that used air transportation services are the population and 200 samples are designated as population representatives. Then the validity test, reliability test, t test, F test, and coefficient of determination test were carried out. And the results stating that health protocol implemented at Soekarno-Hatta International Airport was effective with positive statistical data results and no transmission of the COVID-19.